Formation of Anhydro-sugars in the Primary Volatiles and Solid Residues from Cellulose Fast Pyrolysis in a Wire-Mesh Reactor - Gong, Xun; Yu, Yun; Gao, Xiangpeng; Qiao, Y.; Xu, M.; Wu, Hongwei (American Chemical Society, 2014)
The unique design of wire-mesh reactors (WMR) enables the collection of primary volatiles with minimized secondary reactions from fast pyrolysis of solid fuels. This paper reports the formation of anhydro-sugars in both primary volatiles and solid residues from the fast pyrolysis of microcrystalline cellulose in a WMR. Under fast pyrolysis, cellulose is rapidly converted into an intermediate phase, and the maximal yield of the water-soluble intermediates achieved in this study is ~21% on a carbon basis at 450 °C, much higher than those achieved in other pyrolysis reactor systems. The solid residue consists of sugar and anhydro-sugar oligomers with a wide range of degrees of polymerization (DPs). However, only anhydro-sugars with DPs up to 3 can be identified in the primary volatiles, and the presence of these anhydro-sugars is evident even at 300 °C. Because of high boiling points, cellobiosan and cellotriosan are impossible to be released into the vapor phase via evaporation under the conditions. These high-DP anhydro-sugars are also unlikely formed as a result of oligomerization of levoglucosan in the vapour phase because such secondary reactions are minimized in the WMR. Therefore, cellobiosan and cellotriosan are most likelyreleased into the vapor phase as aerosols, driven by the ejection mechanism (i.e., carryover by the intensive release of volatiles). Among the anhydro-sugars in the primary volatiles, levoglucosan has yields of 27-44% (on a weight basis) depending upon pyrolysis temperature, while cellobiosan and cellotriosan have yields of 3-9 and 1-2%, respectively. This leads to the highestselectivity of 34-60% (on a weight basis) in the condensed liquid product for levoglucosan. The yields of anhydro-sugars initially increase with the pyrolysis temperature and achieve the maximal value between 400 and 450 °C. Further increases in the pyrolysis temperature lead to substantial reductions in the yields of anhydro-sugars in the primary volatiles (although the yield ofliquid product remains unchanged), indicating the increased formation of water-insoluble compounds in the primary volatiles at increased temperatures.